Formation of tolerant attitude towards students with disabilities in the university environment - Tatyana Ostryanko (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
In the article the content of the process of formation of tolerant attitude towards young people with disabilities among students on the basis of analysis of the results of research is defined. The author sets out the basic principles of tolerance, in particular the principle of purposefulness; correlation between the education of tolerance and social position; considering individual characteristics of gender and age; and holding personality in respect; reliance on the positive in the educational process. Pedagogical conditions of formation of tolerant attitude among the students are formulated.
Keywords: tolerance; formation of tolerant attitudes; principles; pedagogical conditions